KAJIAN AUTEKOLOGI Areca vestiaria Giseke PADA HUTAN PEGUNUNGAN BAWAH NGATA TORO KAWASAN TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - Andi Wirdani Pettalolo; Wahyu Harso; Ramadanil Pitopang (Biocelebes, 2020)
The research entitled Autecolgical study of Areca vestaria in Sub-Montane Forest Lore Lindu National Park at Toro village area has been conducted from April to May 2016. The objective of the research was to know the biotics and abiotics factor arround the habitat of Areca vestiaria. The results showed that The highest important value index (IVI) of tree, sapling, pole and seedling species wereFicus ampelos (68.69%), Aphanaximis polistachy (40.01%), Ardisia lateriflora (31.73%) and Ardisia lateriflora (19.23%) respectively. The insects actively interacted with A. vestaria were black ant and bee. Based on soil analyzed indicated that pH of soil 6.6 while N, P and organic matter concentration were 0.26, 0.207 mg/g and 76.1% respectively. A. vestaria grew under light intensity of 540.4 lux, humidity of 76.1% and average daily temperature of 24.4%.